Knowledge, Attitude, and Practices of Moroccan Retail Pharmacists towards Veterinary Medicines - Zeinab Snoussi; Samir Ahid (Hindawi Limited, 2022)
This is the first study conducted in Morocco to assess knowledge, attitude, and practices of retail pharmacists regarding veterinary medicines. It is a cross-sectional study. Two types of multiple-choice questionnaires were distributed to pharmacists depending on whether or not they dispense veterinary medicines. A total of 143 pharmacists were involved in this study. The percentage of retail pharmacists who dispensed veterinary medicines was estimated at 23.1%. Less than half of respondents were highly satisfied regarding their knowledge of veterinary pharmacy. Besides, 39.4% of retail pharmacists were at ease giving advice in general while dispensing veterinary medicines, and 73% were knowledgeable on parasiticides. Approximately, 94% of retail pharmacists expressed their need to improve their knowledge of veterinary pharmacy. Our study also revealed that 48.5% of pharmacists dispensed veterinary medicine daily. This study demonstrated that involvement of retail pharmacists in dispensing veterinary medicines was poor. The need for training programs on veterinary pharmacy expressed by Moroccan retail pharmacists was high.